Comparative evaluation of shear bond strength and nanoleakage of conventional and self-adhering flowable composites to primary teeth dentin - Priyanka Sachdeva; Mousumi Goswami; Darrel Singh (Wolters Kluwer Medknow Publications, 2016)
Background: The latest advancement in adhesive dentistry is the development of self adhering flowable composite resin which incorporates the self-etch adhesion technology to eliminate the steps of etching, rinsing, priming and bonding. Few studies have addressed resin bonding to primary teeth. Aim: The aim of this study was to compare the shear bond strength and nanoleakage of conventional and self adhering flowable composites to primary teeth dentin. Settings and Design: This study was conducted in the Department of Pedodontics and Preventive Dentistry, I.T.S Dental College, Hospital and Research Centre, Greater Noida; in association with the Department of Mechanical Engineering, I.T.S Engineering College, Greater Noida; and the Advanced Instrumentation Research Facility (AIRF), Jawaharlal Nehru University, New Delhi. Materials and Methods: Sixty of the ninety primary teeth were evaluated for shear bond strength and thirty for nanoleakage. The samples were divided into three groups; Group I - Dyad Flow (Kerr), Group II - Fusio Liquid Dentin (Pentron Clinical Technologies) and Group III - G-aenial Universal Flo (GC). Shear bond strength was determined using a universal testing machine. Nanoleakage pattern was observed under scanning electron microscope. Results: The shear bond strength of conventional flowable composite was significantly greater than self adhering flowable composite (p<0.05). Nanoleakage scores of both conventional and self adhering flowable composites were comparable. Conclusions: Self adhering flowable composites combine properties of composites and self etch adhesives, eliminating the need for separate bond application that simplifies direct restorative procedure. The evolution of self adhering materials could open new horizons for pediatric dentistry.